The Review of Methods for Analyzing Economic Sanction Effectiveness and Their Adaptation to Assessing the Impact on Russia in New Information Context - A. A. Chernykh (Вестник Российского экономического университета имени Г. В. Плеханова)
The article provides a complex review of methods, which can be used to assess efficiency of anti-Russian economic sanctions focusing on problems and opportunities dealing with their application. The relevant global experience and experience of Russia in 2014-2021 were used to resolve problems of sanction classification and the idea of sanction effectiveness, as well as assessing sanction impact on economy and certain markets of target-countries, for example Russia. Apart from identifying negative aftereffects of sanctions, positive consequences were also shown. In 2022 the situation drastically changed due to unprecedented harsh economic sanctions introduced against Russia, which made the use of traditional methods of appraisal impossible. The author described restrictions of using open data, including the access to national indicators and explained why traditional methods can lead to false conclusions. In spite of new challenges for researchers, stock market still provides certain possibilities for assessing sanction impact on Russian economy.